Spatial Evaluation of Existing Agricultural Land-Use Conformity Against Spatial Pattern Planning to Mitigate Land Conversion in Babulu District - Hanif Ilman Maulana; Yoga Toyibulah (CV. Komunitas Dunia Peternakan, 2026)
Spatial utilization constitutes a critical dimension of regional development, frequently characterized by discrepancies between planned spatial structures and their empirical realization on the ground. This study aims to evaluate the degree of conformity between the 2023–2043 spatial pattern plan and the existing agricultural land use in Babulu District, Penajam Paser Utara Regency. The methodological framework employs a Geographic Information System (GIS)-based spatial analysis approach through overlay techniques integrating spatial pattern planning maps with agricultural land use data derived from satellite imagery interpretation, particularly Sentinel-2A imagery. The research procedures encompass data processing, on-screen digitization, overlay analysis, and field verification to assess the accuracy level of land use interpretation results. The findings indicate that the total area of existing agricultural land use covers 8,235.54 hectares, of which 7,898.61 hectares are classified as conforming areas, while 336.94 hectares are non-conforming. Sebakung Jaya Village exhibits the largest extent of conforming agricultural land, reaching 1,422.42 hectares (99.96%), whereas the highest degree of agricultural land-use inconsistency occurs in Gunung Makmur Village (197.97 hectares or 34.33% of its existing area). The accuracy assessment based on Groundcheck verification yielded an accuracy value of 83.3% for the agricultural class based on 12 observation points. Several factors contributing to spatial non-conformity include expansion of built-up areas driven by population growth, lack of synchronization with the latest village development, and weak zoning regulation enforcement. The study concludes that while agricultural space protection in Babulu District is relatively strong, local inconsistencies require immediate integration into the upcoming detailed spatial plan (RDTR) to support food security in the new national capital (IKN) buffer zone